Body Mass Index Combined With Possible Sarcopenia Status Is Better Than BMI or Possible Sarcopenia Status Alone for Predicting All-Cause Mortality Among Asian Community-Dwelling Older Adults - Chalermsri, Chalobol; Aekplakorn, Wichai; Srinonprasert, Varalak (Frontiers in Nutrition, 2022)
Background: Body mass index (BMI) and sarcopenia are common indicators of nutritional status. Possible sarcopenia, defined as low muscle strength or performance, was recently introduced by the Asian Working Group for Sarcopenia (AWGS) 2019. We investigated for association between all-cause mortality and BMI combined with possible sarcopenia severity in Asian older adults. Methods: This study included a subpopulation (8,195 participants aged ≥60 years; male gender: 49.4%; mean age: 69.2±6.8 years) from the Fourth Thai National Health Examination Survey (2008). BMI was classified using Asia-Pacific cut-offs. Possible sarcopenia was defined using quadriceps strength (AWGS 2019), and sarcopenia severity was determined using study population quartile cut-offs. All-cause mortality data was derived from the national vital registry in 2020. Results: The prevalence of underweight status and possible sarcopenia was 11.8% and 38.9%, respectively. Multivariate analysis showed underweight individuals with severe possible sarcopenia to be at highest risk for increased mortality (adjusted hazard ratio [aHR]: 3.98, 95% confidence interval [CI]: 2.89-5.48), and higher risk was found in men compared to women (aHR: 5.35, 95%CI: 1.19-8.97). Obese status without sarcopenia was an independent protective factor (aHR: 0.61, 95%CI: 0.38-0.97). Conclusion: BMI combined with possible sarcopenia severity is a better predictor of mortality risk than either parameter alone.